Penerapan Model Pembelajaran Think-Pair-Share dengan Peta Konsep untuk Meningkatkan Hasil Belajar Studi Kasus: SMA Negeri 1 Menganti-Gresik - Mujiono Mujiono (Nidhomul Haq, 2018)
Application of cooperative model type think-pair- share using concept maps can increase teacher’s activity, students’ activities and learning outcomes.The result of the study showed that  the  application  of  that  cooperative  model  can  improve  teacher’s  activities.  The average of the increasing at each cycle are the first cycle  3.3, the second cycle 3.5, and the third cycle 3.6 and the increase in the implementation of student activities at each cycle is the first cycle 3, the second cycle 3.2, and the third cycle 3.5. Improvement of student learning outcomes as follows pretest 67.5, the first cycle 86, second cycle 88, and the third cycle 93. Students' response toward the application of cooperative learning model type think-pair-share using concept map learning strategy on worksheet of service enterprise is very positive. The constraint that appeared in this research was about lower student self confidence in making an idea. It can be inferred, the student’s learning outcome in the subject of accounting worksheet in service enterprise can be increased by applying cooperative learning model with think-pair-share type and concept map strategy.